Sri Aman District Office (PDSA) / Dayang Nurahanim Abang Ramlan - Abang Ramlan, Dayang Nurahanim (University Technology MARA Sarawak, 2017)
District Administration in Simanggang, known as Sri Aman today, may have been introduced asearly as 1846 when the Lupar's territory handed over to James Brooke. Then, James Brooke built Fort James in Nanga Skrang in 1849 to face the threat of opponents. This forced the government to build a fort named Fort James in Nanga Skrang in 1849. Fort James in Skrang is the first and the beginning ofthe existence of the Regional Office which provides the needs of the market is much needed by the district administration. Government post in Nanga Skrang only for the short while and then left after only fort built in Simanggang Alice. Construction and completion of Fort Alice in 1864 was the basis for the government today for both parts and Sri Aman District (District Office Official Portal, January 2017).